Meningkatkan Kemampuan Pemahaman Mendengarkan Siswa Menggunakan Video Animasi - Yubellia Hildegardis Ratu; Endang Susilawati; Urai Salam (Journal of Education and Teaching (JET), 2024)
This current research aims to improve students' listening comprehension skills using animation videos. The classroom action research was conducted at Senior High School 2 in Teriak, Bengkayang, with 34 first-grade students participating. These students faced challenges in comprehending word meanings, implicit messages, and explicit messages in audio. Over two research cycles, findings indicated that animation videos significantly enhanced students' understanding of simple past tense verbs. The videos provided repeated exposure to vocabulary and, through the combination of moving pictures and audio, helped students better grasp both implicit and explicit messages of the stories. Consequently, the researchers concluded that students' listening comprehension skills can be effectively improved through the use of animation videos.